Chronic liver disease due to hepatitis C. Issue 6884 (17th April 1993) - Levi, S; Foster, C; Hodgson, H J; Ward, K N; So, A; Garson, J A; Waxman, J; Swirsky, D
Abstract : The low concentration of hepatitis C virus in the blood of infected patients has made it difficult to detect. Infected patients can now be identified by using more sensitive immunoassays and amplification of viral RNA by the polymerase chain reaction. Nevertheless, the virus remains difficult to eliminate. We present the case of a woman with a history of autoimmune haemolytic anaemia, thrombocytopenia, and common variable immunodeficiency who developed chronic hepatitis.